2022
DOI: 10.1016/j.jpain.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief Reverses Hippocampal Abnormalities in Trigeminal Neuralgia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 105 publications
1
26
0
Order By: Relevance
“…Although no effects were shown in subnucleus volumes versus disease duration, this correlation should be explored further in future work with a larger cohort to validate previous findings which suggest that duration of symptoms may be linked to structural alterations in TN 26 . Future work evaluating the intensity of TN attacks, presence of sensory deficit, and allodynia can further elucidate the relationship between pain and structural changes in TN.…”
Section: Limitations and Future Directionsmentioning
confidence: 68%
See 3 more Smart Citations
“…Although no effects were shown in subnucleus volumes versus disease duration, this correlation should be explored further in future work with a larger cohort to validate previous findings which suggest that duration of symptoms may be linked to structural alterations in TN 26 . Future work evaluating the intensity of TN attacks, presence of sensory deficit, and allodynia can further elucidate the relationship between pain and structural changes in TN.…”
Section: Limitations and Future Directionsmentioning
confidence: 68%
“…Advanced imaging studies are increasingly being applied to study TN. Studies have shown structural changes in trigeminal nerves [17][18][19][20] and limbic structures [21,[23][24][25][26] in the presence of TN pathology. In this study, ultra-high field MRI provided excellent resolution of the trigeminal nerves as well as granular subregions of the hippocampus, amygdala, and thalamus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study found that volume recovery or normalization reveals sex-specific hippocampus plasticity in TN, with females experiencing a higher volumetric increase than males. They hypothesized that hippocampus shrinkage in TN is caused by pain, and that proper treatment can correct these anomalies [62].…”
Section: Clinical Studies Related To Trigeminal Neuralgiamentioning
confidence: 99%